1993
DOI: 10.1002/art.1780360813
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the major histocompatibility complex in french canadian and non–french canadian caucasians with systemic lupus erythematosus

Abstract: Objective. To investigate and compare the predisposing role of major histocompatibility complex (MHC) genes in systemic lupus erythematosus (SLE) in French Canadian and non-French Canadian (mainly AngloSaxon descent) Caucasian subjects.Methods. HLA-A, B, C (serology), DR, and DQ (restriction fragment length polymorphism [RFLP] typing) were determined. RFLP defining a large C4A,21-OHA deletion (Tuq I C4) and an Nco I tumor necrosis factor a (TNFa) RFLP were analyzed in 91 Caucasian Canadians and 91 ethnically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 50 publications
2
28
1
1
Order By: Relevance
“…This could be due to the presence of genetic heterogeneity. 20,21,31,32 In this study, the C4A*Q0 allele was found in two out of the 130 control groups, while C4B*Q0 was present in two out of the 130 SLE patients. These results however, did not show any significant association to the occurrence of SLE disorder.…”
Section: Discussionmentioning
confidence: 76%
“…This could be due to the presence of genetic heterogeneity. 20,21,31,32 In this study, the C4A*Q0 allele was found in two out of the 130 control groups, while C4B*Q0 was present in two out of the 130 SLE patients. These results however, did not show any significant association to the occurrence of SLE disorder.…”
Section: Discussionmentioning
confidence: 76%
“…The B8-DR3 haplotype, frequently detected in SLE and other autoimmune syndromes (42,43), was significantly increased in all patient groups. Although it was not associated with specific features of autoimmunity, there was a high frequency of this haplotype in the small number of anti-Roϩ patients.…”
Section: Discussionmentioning
confidence: 88%
“…29,30 Our previous study comparing French Canadian and non-French Canadian Caucasians with SLE to healthy ethnically matched control subjects, demonstrated that the strongest association with disease susceptibility in the non-French Canadian population was the extended haplotype HLA-B8, DR3, Dw24, DQ2, C4A gene deletion. 31 In contrast, the C4A gene deletion was not increased above controls in French Canadians and when the deletion was present, it was not strongly associated with the above noted haplotype. The strongest association in the French subset was with HLA-DQ6 imparting a relative risk of 2.6.…”
Section: Introductionmentioning
confidence: 77%